ANALYSIS OF PRO-POOR GROWTH ON POVERTY IN SOUTH SUMATRA - Cristover, Daniel; Satriani, Jeanne Aleysia; Siregar, Anandhita; Natasyha, Zaskia Kurnia (Jurnal Widya Publika, 2025)
Poverty plays a critical role in shaping the economic development of a region, as it directly affects income distribution and access to resources. In South Sumatra, for example, while poverty declined from 2017 to 2022, the region’s economic growth showed signs of stagnation. The Gini coefficient, which measures income inequality, remained largely unchanged during this period, raising concerns about the inclusivity of the growth. This paradox prompted the author to conduct a study to explore the relationship between economic growth and poverty alleviation in South Sumatra and to determine whether the region's growth could be classified as "Pro-Poor." Specifically, the study aimed to assess the Pro-Poor Growth (PPG) level in South Sumatra’s economy from 2017 to 2022, while also testing classical assumptions related to poverty reduction. Panel data from 17 districts in South Sumatra were collected and analyzed over the five-year period. The findings revealed that the impact of economic growth on poverty reduction was less significant than anticipated. The Pro-Poor Growth indicator (IGP) largely showed insignificant results, indicating that economic growth during this period did not translate effectively into poverty alleviation. These findings highlight the need for more targeted policies to ensure that growth benefits reach the poorer segments of society and address the structural challenges preventing more inclusive growth in South Sumatra.